In the frame, road map for Australian sport on an uncertain journey through COVID-19 - Hughes, D. (Journal of Science and Medicine in Sport, 2020)
The Australian Institute of Sport (AIS), began work in early April 2020 on the "AIS Framework to reboot sport in a COVID-19 environment" (the AIS Framework). One of the key principles underpinning the AIS Framework is that the resumption of sport and recreation activities should not compromise the health of individuals or the community. Education of all stakeholders in the sport sector, with the aim of improving health literacy around COVID-19, is central to the AIS Framework. It will be personal behaviours, not just extensive testing that will determine whether sport can resume without compromising the health and safety of the community. The AIS-Framework is intended to assist sporting organisations and individuals, from high performance/professional sport organisations to individual recreational athletes, in the complex decisions involved in moving towards normalisation of sport function. One of the many challenges faced in constructing the AIS Framework was the paucity of research, particularly in athletic populations. The AISFramework is based on the latest data being published out of heavily affected areas in China, Europe and United States, extrapolated into the sporting context by specialists in sport and exercise medicine, infectious diseases and public health.